Efficacy and Safety of Intravenous Secukinumab in Patients With Active Axial Spondyloarthritis: Results From a Randomized, Placebo-Controlled, Phase 3 Study - Deodhar, Atul; Supronik, Jerzy; Kivitz, Alan; Valenzuela, Guillermo; Kapur, Karen; Rohrer, Susanne; Dokoupilová, Eva; Richards, Hanno B; Pavelka, Karel (Arthritis & rheumatology (Hoboken, N.J.), 2025)
OBJECTIVE: Our goal was to assess the efficacy and safety of intravenous (IV) secukinumab for the treatment of adults with active axial spondyloarthritis (axSpA) in INVIGORATE-1. METHODS: INVIGORATE-1 (NCT04156620) was a randomized, double-blind, parallel-group, phase 3 trial in patients with active axSpA (either radiographic or nonradiographic). Patients were randomized one to one to receive IV secukinumab (6 mg/kg at baseline followed by 3 mg/kg every four weeks) or IV placebo for 16 weeks. After week 16, patients randomized to placebo were switched to IV secukinumab (3 mg/kg every four weeks), and patients randomized to secukinumab continued treatment through week 52. The primary endpoint was the Assessment of SpondyloArthritis International Society (ASAS40) response at week 16. Safety was evaluated through week 60. RESULTS: Among patients initially randomized to IV secukinumab (n = 264) or placebo (n = 262), 86.0% and 88.9% completed the entire 60-week study period, respectively. A higher proportion of patients receiving secukinumab versus placebo met the primary endpoint (ASAS40 response) at week 16 (40.9% vs 22.9%; P < 0.0001). By week 24, patients who switched from placebo to secukinumab at week 16 achieved ASAS40 response rates comparable to those in patients originally randomized to secukinumab. All secondary efficacy endpoints were met at week 16, and responses were sustained through week 52. No new or unexpected safety signals were observed with IV secukinumab. CONCLUSION: IV secukinumab was effective for the treatment of adults with active axSpA over 52 weeks. The safety profile was consistent with that in previous reports on subcutaneous secukinumab.
Keywords: dvojitá slepá metoda; Double-Blind Method; axiální spondyloartritida; výsledek terapie; Administration, Intravenous; monoklonální protilátky; Middle Aged; mužské pohlaví; Infusions, Intravenous; Antibodies, Monoclonal; intravenózní infuze; Adult; intravenózní podání; ženské pohlaví; Humans; antirevmatika; Antibodies, Monoclonal, Humanized; humanizované monoklonální protilátky; lidé středního věku; Antirheumatic Agents; dospělí; Axial Spondyloarthritis; Female; Treatment Outcome; lidé; Male